A comparative review of the CEFR and CET4 writing assessment with insights from task complexity theories - Li, Changlin; Nik Aloesnita, Nik Mohd Alwi; Mohammad Musab, Azmat Ali (www.msocialsciences.com, 2025)
The CEFR level descriptors are applied globally for language assessment, which is already aligned with IELTS, TOEFL, etc. Meanwhile, the CET4 is essential in language learning and teaching proficiency assessment in China. Building on previous research, this study examines the relationship between the CEFR level descriptors and the CET4 writing rubrics, mainly focusing on the essay writing assessment within the past decade. Despite the broad utilisation of the CET4 in universities, its comparison with the CEFR level descriptors remains underexplored. Based on this situation, the study investigates task complexity theories, automated and manual scoring systems, and recent studies about essay writing. Findings indicate that the CET4 writing scores correspond roughly to CEFR levels A1–B2, though comparisons with higher proficiency levels (C1–C2) remain inconsistent. While automated scoring systems reliably evaluate basic linguistic dimensions, they struggle to assess more aspects, such as description, argument, task relevance, and clarity dimensions, under the CEFR and CET4 writing assessments. Furthermore, the automated scoring systems lack the capacity to capture the nuanced features of advanced writing. These findings underscore the necessity of human evaluation, particularly in essay writing content assessment, while highlighting opportunities to refine grading methodologies and task design to enhance essay writing instruction.